Correlation of Early Nutritional Supply and Development of Bronchopulmonary Dysplasia in Preterm Infants <1,000 g - Thiess, Theresa; Lauer, Tina; Woesler, Annika; Neusius, Janine; Stehle, Sandro; Zimmer, Klaus-Peter; Eckert, Gunter Peter; Ehrhardt, Harald (Frontiers in Pediatrics, 2021)
Background: Bronchopulmonary dysplasia (BPD) has multifactorial origins and is characterized by distorted physiological lung development. The impact of nutrition on the incidence of BPD is less studied so far. Methods: A retrospective single center analysis was performed on n=207 preterm infants <1000 g and <32 weeks of gestation without severe gastrointestinal complications to assess the impact of variations in nutritional supply during the first two weeks of life on the pulmonary outcome. Infants were grouped into no/mild and moderate/severe BPD to separate minor and major limitations in lung function. Results: After risk adjustment for gestational age, birth weight, sex, multiples and antenatal steroids, a reduced total caloric intake and carbohydrate supply as the dominant energy source during the first two weeks of life prevailed statistically significant in infants developing moderate/severe BPD (p<0.05). Enteral nutritional supply was increased at a slower rate with prolonged need for parenteral nutrition in the moderate/severe BPD group while breast milk provision and objective criteria of feeding intolerance were equally distributed in both groups. Conclusion: Early high caloric intake is correlated with a better pulmonary outcome in preterm infants <1000 g. Our results are in line with the known strong impact of nutrient supply on somatic growth and psychomotor development. Our data encourage paying special attention to further decipher the ideal nutritional requirements for unrestricted lung development and promoting progressive enteral nutrition in the absence of objective criteria of feeding intolerance.